2019
DOI: 10.2147/ce.s187499
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tedizolid phosphate for the treatment of acute bacterial skin and skin-structure infections: an evidence-based review of its place in therapy</p>

Abstract: Introduction Tedizolid phosphate is an oxazolidinone approved for the treatment of acute bacterial skin and skin-structure infections (ABSSSIs) and active against methicillin-resistant Staphylococcus aureus . Aims The objective of this article was to review the evidence for the efficacy and safety of tedizolid phosphate for the treatment of ABSSSI. Evidence review Approval of tedizolid phosphate for the treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Our results on S. aureus biofilm, together with previously available data ( Bassetti et al, 2019 ; Carvalhaes et al, 2019 ), suggest a complementary activity of this combination. Indeed, rifampicin is known to be able to disaggregate S. aureus biofilm, while tedizolid has a good antimicrobial activity against planktonic bacteria and it has been demonstrated that inhibits S. aureus biofilm formation ( Delpech et al, 2018 ; Abad et al, 2019 ).…”
Section: Discussionsupporting
confidence: 85%
“…Our results on S. aureus biofilm, together with previously available data ( Bassetti et al, 2019 ; Carvalhaes et al, 2019 ), suggest a complementary activity of this combination. Indeed, rifampicin is known to be able to disaggregate S. aureus biofilm, while tedizolid has a good antimicrobial activity against planktonic bacteria and it has been demonstrated that inhibits S. aureus biofilm formation ( Delpech et al, 2018 ; Abad et al, 2019 ).…”
Section: Discussionsupporting
confidence: 85%
“…It is possible that there was a cumulative effect of oxazolidinone therapy, combining the 8-month tedizolid course with 3-weeks prior exposure to linezolid. Tedizolid has compared favourably to linezolid in studies of ABSSIs [11] . It had non-inferior efficacy and reduced risk of some side effects, including thrombocytopenia, though it is important to note these studies tested short-term therapy (less than 14 days).…”
Section: Discussionmentioning
confidence: 99%
“…The most common side effects were headache, nausea and QT prolongation [62,63]. It has not been FDA approved for ABSSSI yet for safety concerns [64][65][66][67][68] (Table 1).…”
Section: Iclaprimmentioning
confidence: 99%